(untitled) (Health and Addictions/Salud y Drogas, 2018)
Excessive alcohol consumption by college students is being recognized more and more, and its negative effects justify the implementation of prevention programs. Positive expectancies of alcohol are frequently acquired in adolescence and assume an important role in young-adult consumption patterns. This paper describes validation of the brief version of the Alcohol Expectancy-Adolescent Questionnaire (AEQ-AB) carried out with a sample of 317 freshman-year college students at a public Portuguese University. Results of confirmatory factor analysis, invariance and internal consistency showed some difficulties in the internal structure of the questionnaire. The two-factor model did not fit because no factor emerged to represent the negative expectation items. A single-factor structure was assumed and its invariance by gender was confirmed, as well as good internal consistency. The validity criterion showed positive and negative correlations with several variables depending on whether they were positively or negatively related to alcohol consumption. The oldest students and students drinking alcohol from early ages had the lowest expectancy of positive effects of the use of alcohol. With regard to academic performance, freshmen with a high GPA showed strong expectancies for the positive effects of alcohol. Positive correlations have been observed between positive alcohol expectancy and consumption levels. Further studies are necessary to include a negative dimension in the measure of expectancies of alcohol consumption.